The role of hydrogen for future sustainable energy systems: development strategies for Brazil and Italy - Benecchi, Filippo Maria (2021)
Many countries have identified hydrogen, in its “green version”, as a key ally in the race to adopt sustainable, zero-emission energy systems. As a result, national strategies have been developed for local hydrogen supply chains and markets. Through the electrolysis process and the use of renewable sources, H2 can be produced without polluting. The uniqueness of the energy vector, including the possibility of being transported over long distances without losing energy content, makes it an attractive option. Given the premisses, Brazil and Italy should not miss this opportunity, especially considering that they could play important roles in the global market that is being formed thanks to their geographical peculiarities. Hence, the purpose of this qualitative study is to advise on a set of guidelines for the development of the two countries’ national strategies. First, the research focuses on technical aspects to offer a detailed understanding of the characteristics of hydrogen and its strengths in the energy field, also presenting the existing challenges that obstacle its diffusion. Next, national strategies already developed and implemented are analysed, identifying trends that are defining the global hydrogen market. And finally, also by making use of interviews with local experts, proposals are drawn up to guide the construction of national hydrogen development strategies for Brazil and Italy, with a view to maximising the achievable results.